Micro‐CT Evaluation of Ceramic Inlays: Comparison of the Marginal and Internal Fit of Five and Three Axis CAM Systems with a Heat Press Technique. Issue 1 (29th September 2016) - Alajaji, Norah K.; Bardwell, David; Finkelman, Matthew; Ali, Ala
Abstract: Objectives: To evaluate the marginal and internal adaptation of CAD/CAM lithium‐disilicate inlay restorations fabricated by two milling systems (Five and Three‐axis), and a traditional heat‐press technique. Methods: Fifteen premolar teeth with an MOD cavity preparation were fabricated. Lithium‐disilicate inlay restorations were obtained by three fabrication techniques and fitted to their dies ( n = 15/gp) as follows: Group‐1, three‐axis milling system, Group‐2, five‐axis milling system, Group‐3, conventional heat‐press technique. Gaps were evaluated by X‐ray microtomography. Marginal gap (MG), occlusal‐marginal gap (OMG), proximal‐marginal gap (PMG), gingival‐marginal gap (GMG), absolute marginal discrepancy (AMD), axial‐internal gap (AIG), and occlusal‐internal gap (OIG) were evaluated at 120 different points per inlay. Data were analyzed using repeated measures ANOVA. Pairwise comparisons were conducted for post‐hoc testes and the Bonferroni correction was used to adjust for multiple comparisons ( α = 0.007). Results: The heat‐press group demonstrated significantly smaller mean‐values amongst all outcomes compared with CAD/CAM groups except for GMG, where there was no statistically significant difference between groups in the ANOVA ( p = 0.042). Within the CAD/CAM groups, the five‐axis group showed significantly lower OMG mean‐value compared with the three‐axis group p < 0.001, and lower AIG mean‐value compared with the three‐axis group p < 0.001. There was no significant difference between the five‐axis and the three‐axis groups' AMD, MG, PMG, and OIG locations. Conclusion: Different fabrication techniques affected the marginal and internal adaptation of ceramic inlay restorations. The heat‐press group showed the best marginal and internal adaptation results; however, in every group, all samples were within the clinically acceptable MG limit (100 μm). Clinical Significance: The marginal fit and internal adaptation of inlay ceramic restorations fabricated by a five‐axis milling system have not been tested or compared with those fabricated by three‐axis machines and the conventional heat‐press method. The preferred method of inlay fabrication, whether in the lab or chair side, may be influenced by the results of this study and could affect future clinical decision‐making. (J Esthet Restor Dent 29:49–58, 2017)